Novel Two-Chamber Method for High-Precision TCR Determination of Current Shunts—Part I - Petar Mostarac; Roman Malarić; Hrvoje Hegeduš; Alan Šala (Sensors)
The temperature coefficient of resistance (TCR) plays a crucial role in ensuring the functional accuracy of systems. This article examines the determination of TCR for precision current shunts and presents a novel two-chamber method. The method uses a two-chamber setup for high-precision temperature control, which ensures a reduction in measurement uncertainty when determining the TCR. The two-chamber method is applicable for resistance ratios from 0.1 to 10. The advantages of the proposed method are the improvement of the stability of the reference shunt and the reduction of the measurement uncertainty, and thus a more accurate determination of the TCR. In Part I, the influence of the individual parameters on the determination of the measurement uncertainty of the measured TCR is analyzed.